Protection Side Chain of Lysine by Host-Affinity Molecules during Solid Phase Peptide Synthesis in Aqueous Phase - Yong, Ma (Journal of Peptides, 2024)
A new approach to protecting the side chain of lysine during solid-phase peptide synthesis in an aqueous environment is explored. The objectives of this study are twofold: 1) to reduce the consumption of chemical solvents in peptide synthesis, and 2) to lower the costs associated with lysine side chain protection. In an effort to minimize the usage of organic solvents in amino acid side chain protection for peptide synthesis,18-crown-6 molecule (18C6) was introduced as protective agent for Lysine (Lys) side chain protection. 18C6 is utilized to protect ε-amino group of on side chain of Lys in peptide synthesis. 18C6 features cavity at its center. The 18C6 molecules exhibit a unique and distinctive host-guest affinity towards ε-amino group on side chain of Lys. 18C6 bind to Lys side chain through hydrogen bonds with ε-amino group of Lys, eliminating the need for chemical reactions in organic solvents to attach protective molecules to the side chain groups. This simplifies the side chain protection procedure significantly for Lys, reducing the consumption of organic solvents. Consequently, this procedure offers advantages for contributing to a greener planet by minimizing chemical reactions and organic solvent usage. Additionally, the cost of side chain protection of Lys is dramatically reduced.
Keywords: Solid-phase peptide synthesis (SPPS); greener SPPS; protection of side chain of Lys by 18-crown-6 molecule (18C6); 18C6molecule host-guest affinity towards ε-amino group of Lys